2022
DOI: 10.1109/twc.2022.3179232
|View full text |Cite
|
Sign up to set email alerts
|

Beamformed Self-Interference Measurements at 28 GHz: Spatial Insights and Angular Spread

Abstract: We present measurements and analysis of self-interference in multi-panel millimeter wave (mmWave) full-duplex communication systems at 28 GHz. In an anechoic chamber, we measure the self-interference power between the input of a transmitting phased array and the output of a colocated receiving phased array, each of which is electronically steered across a number of directions in azimuth and elevation. These self-interference power measurements shed light on the potential for a full-duplex communication system … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(38 citation statements)
references
References 18 publications
4
33
1
Order By: Relevance
“…In contrast, codebooks created for conventional mmWave systems can deliver high beamforming gain but are not necessarily robust to self-interference if used in full-duplex systems [10]. In fact, this was confirmed in our recent measurement campaign [9] and in our recent work [23], both of which showed that conventional beams typically couple prohibitively high amounts of self-interference if used in a practical full-duplex mmWave system.…”
Section: Analog Beamforming Codebook Design For Full-duplex Mmwave Sy...supporting
confidence: 57%
See 4 more Smart Citations
“…In contrast, codebooks created for conventional mmWave systems can deliver high beamforming gain but are not necessarily robust to self-interference if used in full-duplex systems [10]. In fact, this was confirmed in our recent measurement campaign [9] and in our recent work [23], both of which showed that conventional beams typically couple prohibitively high amounts of self-interference if used in a practical full-duplex mmWave system.…”
Section: Analog Beamforming Codebook Design For Full-duplex Mmwave Sy...supporting
confidence: 57%
“…Since transmission and reception happen simultaneously and in-band, a self-interference channel H ∈ C Nr×Nt manifests between the transmit and receive arrays of the full-duplex BS. Currently, there is not a reliable, measurement-backed model for the self-interference channel H [9], [10]. As such, the design herein is not based on any assumption of H, and we evaluate our design using multiple channel models in Section VII.…”
Section: System Modelmentioning
confidence: 99%
See 3 more Smart Citations